Effect of Varying Curing Times of the High-Intensity Light Emiting Diode (Flashmask P3) on the Shear Bond Strength of Orthodontic Metal Brackets: an In-Vitro Study using Bovine Teeth/Eunice U. Ramos-Musñgi. - Ramos-Musñgi, Eunice U.
The aim of this study was to compare the shear bond strength (SBS) of stainless-steel bracket with varying curing times of Flashmax P3. Fifty-five permanent bovine teeth were collected and randomly divided into five Groups of eleven samples each: (1) conventional LCU at 10 s, (2) Flashmax P3 at 1 sec, (3) Flashmax P3 at 2 sec, (4) Flashmax P3 at 3 sec, (5) Flashmax P3 at 6 sec. Bovine teeth were bonded using Transbond XT and the SBS was measured with Shimadzu Universal Testing Machine at crosshead speed of 1mm/min. The One-way ANOVA and Turkey's Honest Significant Difference Test were performed with significance pre-determined at P<0.05. The overall mean bond strengths were 6.89+1.82, 3.54+ 3.20, 6.14+ 1.74, 7.03+ 1.04, 7.45 + 1.90. for the Groups 1,2,3,4 and 5, respectively. One-way ANOVA test gave an F=6.335 with a P=0.0003. Group 2 was observed to have statistical difference in SBS among all Groups. Adhesive Remnant Inex was also analyzed using Kruskal-Wallis test and found no statistical difference among Groups. The Group 2 (Flashmax P3 at 1 sec) had the lowest mean shear bond strength among all Groups. The shear bond strength between Groups 1,3,4 and 5 (Woodpecker at 10 sec, Flashmax at 3 sec and Flashmax at 6 sec., respectively) were not statistically significant and the result of this study suggest that the use of Flashmax P3 in as short as 2 seconds curing time is statistically comparable to conventional light curing unit at 10 seconds curing resin-based orthodontic adhesives.